Effect of Polyhydroxybutyrate Nano-Particles (PHB-NPs) in Mice Kidney Tissues: Histopathological Investigation (World Journal of Experimental Biosciences, 2023)
Polyhydroxybutyrate (PHB) is a promising substance as it enters different applications such as medical, industrial, and food sectors. It is a safe material to prepare the PHB-nanoparticles (NPs) that are required to pass different chemo-physical reactions that may change its structure. That is why the PHB-NPs are required to assess their toxicity. The objective of the present investigation is to evaluate the cytotoxicity of PHB-NPs in vivo by examining the impact of PHB-NPs and other forms of this compound on kidney tissue. Within the confines of this study, PHB-NPs were synthesized in the laboratory through the application of ultrasound waves to PHB under varying pH conditions. The generation of PHB-NPs was estimated using a scanning electron microscope (SEM). Four cohorts of mice were intraperitoneally injected with 0.5 mg of PHB, PHB-NPs, PHB-cefotaxime (CTX), and CTX. The control group consisted of mice that were intraperitoneally injected with normal saline. The mice were subsequently dissected, and kidney slides from each group were prepared for histopathological examination. The method used in the current study is effective in producing PHB-NPs with diameters ranging from 20 to 35 nm. Furthermore, there was no discernible alteration in the kidney tissues of the mice in the four cohorts when compared to the kidney tissues of the control group. Thus, the present study concludes that there is no observed toxicity or any other adverse effects associated with the administration of PHB, PHB-NP, PHB-NP+CTX, and CTX on the histological characteristics of the experimental animals.